Altered cerebral insulin response in transgenic mice expressing the epsilon-4 allele of the human apolipoprotein E gene. (March 2017) - Traversy, Marie-Thérèse; Vandal, Milène; Tremblay, Cyntia; Tournissac, Marine; Giguère-Rancourt, Ariane; Bennett, A. David; Calon, Frédéric
Highlights: APOE4 carriage potentiates the activation of brain insulin signaling pathway. Insulin induces higher phosphorylation of tau at Ser202 in APOE4 mice. Human APOE4 carriers have higher phosphorylation of tau at Ser202. Defects in brain response may explain insulin poor clinical effect in APOE4 carriers. Abstract: Apolipoprotein E epsilon-4 ( APOEε4 or APOE4 ), an allelic variation of the APOE gene, not only increases the risk of developing the late-onset form of Alzheimer's disease (AD), but also influences the outcome of treatment. Indeed, data from clinical studies show that the beneficial effect of insulin on cognition is blunted in APOE4 carriers. To investigate how APOE impacts insulin response, we assessed the effects of an acute insulin injection in APOE3 - and APOE4 -targeted replacement mice that respectively express the human APOE3 or APOE4 isoform instead of the endogenous murine ApoE protein. We evaluated cognition, insulin signaling and proteins implicated in Aβ transport and tau phosphorylation in the cortex and brain capillaries. We found that a single acute insulin injection increased Akt pSer473 in APOE4 compared to APOE3 mice (+113% versus +78.5%), indicating that APOE4 carriage potentiates activation of insulin upstream signaling pathway in the brain. Insulin also led to decreased concentrations of the receptor for advanced glycation endproducts (RAGE) in brain capillaries in both groups of mice. Moreover, higher phosphorylation of tau at Ser202, one of the key markers of AD neuropathology, was observed in insulin-injected APOE4 mice (+44%), consistent with findings in human APOE4 carriers (+400% compared to non-carriers). Therefore, our data suggest that APOE4 carriage leads to an increased insulin-induced activation of cerebral Akt pathway, associated with higher AD-like tau neuropathology. Our results provide evidence of altered insulin signaling in APOE4 carriers as well as a possible mechanism to explain the absence of cognitive benefit from insulin therapy in these individuals.